2022
DOI: 10.3389/fonc.2022.811508
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion strength and anti-tumor agents regulate vinculin of breast cancer cells

Abstract: The onset and progression of cancer are strongly associated with the dissipation of adhesion forces between cancer cells, thus facilitating their incessant attachment and detachment from the extracellular matrix (ECM) to move toward metastasis. During this process, cancer cells undergo mechanical stresses and respond to these stresses with membrane deformation while inducing protrusions to invade the surrounding tissues. Cellular response to mechanical forces is inherently related to the reorganization of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Some study suggested that mechanical stimulus induced malignant behavior of tumor cells by regulating cytoskeletal signal pathway [22] . Adhesion forces between cells and ECM are correlated with vinculin levels, and increase of the vinculin limits the probability of cell detachment and, therefore, cell motility and migration [23] . Stimulation generated by the stiff substrates from ECM triggered the F-actin skeleton, resulting in viscosity decrease and migration of cancer cells [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Some study suggested that mechanical stimulus induced malignant behavior of tumor cells by regulating cytoskeletal signal pathway [22] . Adhesion forces between cells and ECM are correlated with vinculin levels, and increase of the vinculin limits the probability of cell detachment and, therefore, cell motility and migration [23] . Stimulation generated by the stiff substrates from ECM triggered the F-actin skeleton, resulting in viscosity decrease and migration of cancer cells [24] .…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, the migratory cell ability is accompanied by a decrease in vinculin expression . In recent years, the downregulation of vinculin has been found in several highly metastatic cancer cells, which reminded us of its unique role in metastasis and relapse. However, few efforts about vinculin were made in occupational diseases; the vinculin expression level in plasma has not been studied thoroughly compared with other tissues or cells, either. Plasma vinculin has the potential as the biomarker of atherosclerotic diseases, acute myocardial infarction, age-related macular degeneration, and irritable bowel syndrome (IBS), but it was found to be upregulated in those diseases.…”
Section: Discussionmentioning
confidence: 99%
“…The DEGs that were found in patients with premature ovarian insufficiency were mainly associated with extracellular matrix (ECM)/structural organization, different types of junctions, and various catabolic/metabolic/biosynthetic processes. In addition, cytokine−cytokine receptor interactions, the PI3K-Akt signaling pathway, and the MAPK signaling pathway was also enriched, which have close regulatory effects on cellular mechanical properties ( 10 , 11 ). Zhu et al.…”
Section: Introductionmentioning
confidence: 99%